Nurse prescribing in Iran: postgraduate nursing students’ attitudes, readiness and self-efficacy in patient care - Somayeh Mousavi; Hamidreza Haririan; Hadi Hassankhani; Mahdieh Naeri (Journal of Research Development in Nursing and Midwifery)
Background: In many countries, nurses serve as prescribers in the healthcare system to manage acute and chronic diseases. Nurse prescribing can be affected by specific variables, one of which is the nurses' self-efficacy. This study aimed to determine Iranian postgraduate nursing students’ attitudes and readiness for prescribing and its relationship with their self-efficacy in patient care. Methods: This correlational study was conducted on 220 postgraduate nursing students of Tabriz Faculty of Nursing and Midwifery, Iran, from Dec 2022 to Mar 2023. The total population sampling method was employed to include all students, and data were collected using a three-part questionnaire: demographics, nurse prescribing (attitude, and readiness), and self-efficacy questionnaire. The collected data were analyzed using SPSS-26 software. Descriptive statistics were used to analyze demographics. ANOVA and t-tests were employed to compare mean scores, while the Pearson correlation coefficient measured the linear correlation between data sets. The significance level for all tests was determined to be p <0.05. Results: Postgraduate nursing students displayed a positive attitude (39.49±6.04) and strong readiness (40.49±5.33) for prescribing. They also had a strong sense of self-efficacy (166.57±17.05) in patient care. However, participants received the lowest mean score in their knowledge of pharmacology and the decisiveness dimension of self-efficacy. There was a significant positive correlation between the attitudes (r=0.286, p <0.0001) and readiness (r=0.55, p <0.0001) of participants for prescribing and their self-efficacy. PhD students (p=0.01) and those with more clinical work experience (p=0.02) had a positive attitude towards NP. Male students (p=0.02), PhD students (p=0.03), those with clinical work experience (p=0.04), and those who had prescribed medicine for patients or their families (p=0.006), were also more prepared for NP. PhD students (p=0.001), students with more clinical work experience (p=0.04), and those who had a greater interest in nursing (p=0.005) achieved higher mean self-efficacy scores. Conclusion: Given postgraduate nursing students' positive attitudes toward prescribing, readiness to assume this responsibility, and high self-efficacy for patient care, it is possible to prepare them for this new role by improving their pharmacological knowledge and strengthening their decisiveness skills, especially doctoral nursing students.